Oral FXIIa inhibitor KV998086 suppresses FXIIa and single chain FXII mediated kallikrein kinin system activation - Clermont, Allen C.; Murugesan, Nivetha; Edwards, Hannah J.; Lee, Daniel K.; Bayliss, Natasha P.; Duckworth, Edward J.; Pethen, Stephen J.; Hampton, Sally L.; Gailani, David; Feener, Edward P. (Frontiers in Pharmacology, 2023)
Background: The kallikrein kinin system (KKS) is an established pharmacological target for the treatment and prevention of attacks in hereditary angioedema (HAE). Proteolytic activities of FXIIa and single-chain Factor XII (FXII) zymogen contribute to KKS activation and thereby may play roles in both initiating and propagating HAE attacks. In this report, we investigated the effects of potent small molecule FXIIa inhibitors on FXIIa and single chain FXII enzymatic activities, KKS activation, and angioedema in mice.We examined the effects of 29 structurally distinct FXIIa inhibitors on enzymatic activities of FXIIa and a mutant single chain FXII with R334A, R343A and R353A substitutions (rFXII-T), that does not undergo zymogen conversion to FXIIa, using kinetic fluorogenic substrate assays. We examined the effects of a representative FXIIa inhibitor, KV998086, on KKS activation and both carrageenan-and captoprilinduced angioedema in mice.Results: FXIIa inhibitors designed to target its catalytic domain also potently inhibited the enzymatic activity of rFXII-T and the pIC50s of these compounds linearly correlated for rFXIIa and rFXII-T (R 2 =0.93). KV998086, a potent oral FXIIa inhibitor (IC50 = 7.2 nM) inhibited dextran sulfate (DXS)-stimulated generation of plasma kallikrein and FXIIa, and the cleavage of high molecular weight kininogen (HK) in human plasma. KV998086 also inhibited rFXII-T mediated HK cleavage (p<0.005) in plasma from FXII knockout mice supplemented with rFXII-T and stimulated with polyphosphate or DXS. Orally administered KV998086 protected mice from 1) captopril-induced Evans blue leakage in colon and laryngotracheal tissues and 2) blocked carrageenan-induced plasma HK consumption and paw edema.Conclusions: These findings show that small molecule FXIIa inhibitors, designed to target its active site, also inhibit the enzymatic activity of FXII zymogen. Combined inhibition of FXII zymogen and FXIIa may thereby suppress both the initiation and amplification of KKS activation that contribute to hereditary angioedema attacks and other FXII-mediated diseases.